Sixth-Month Perinatal Outcomes of Anemic Pregnancies - Emel Kıyak Çağlayan; Öznur Küçük; Ayşe Yeşim Göçmen; Levent Seçkin; Ayla Aktulay; Yaprak Engin Üstün (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we retrospectively compare the outcomes of anemia in 3rd trimester pregnant women who applied to our clinic, in terms of maternal factors and its fetal effects, in 0 and 6th months. STUDY DESIGN: 139 cases admitted to our clinic during December 2010 - May 2012 due to pregnancy in their 3rd trimester and were diagnosed with anemia and whose records were available were included in the study. The pregnant women were divided into two groups according to their hemoglobin (Hb) levels; hemoglobin levels below 11 g/dL formed the anemia group (AG Hb<11 g/dL) and those above were the non-anemia group (NAG Hb ›11 g/dL). Maternal age, occupation, number of live births, Hb and hematocrit (Hct) levels, mode of delivery, labor time, and head circumference, weight and height of infants at birth and 6th month were compared. RESULTS: Anemia was determined in 69 pregnant women (49.6%). No significant difference among the groups in terms of age and parity was detected. Anemia was found to be higher in housewife mothers (p=0.0001). No difference in terms of birth weight and height was detected among the babies of mothers of the two groups, but the head circumference of the babies from anemic mothers were determined to be significantly lower (p= 0.0001). In terms of the 6th month outcomes; weight, height and head circumference of babies from anemic mothers were found to be significantly lower (p=0.0001). Risk analysis has determined a negative correlation between anemia and fetal development at 6th month. CONCLUSION: There is a negative correlation between anemia and preterm delivery week, fetal development and small head circumference at birth. Therefore maternal candidates with high rates of anemia such as housewives should be closely monitored during pregnancy and in the postpartum period for fetal development.